The Policy of Federal Student Loans: Looking Backward and Looking Forward - Aaron Mohr (Washington University Journal of Law & Policy, 2017)
This Note addresses the discrepancies between inflation rates and the cost of higher learning, particularly as a new generation of students finds it more difficult to pursue additional education because student loan burdens continue to outpace real wages. Mohr examines various contributing factors in this imbalance, including rises in tuition costs, the widespread availability of loans, and the difficulty in discharging these debts, to identify the source of the problem. Mohr suggests that the underlying issue is the rising costs of higher education as a function of the availability of loans, and recommends a system of limits on borrowing that would allow costs to increase closer to inflation rates.
Keywords: student loans; debt; federal loans; bankruptcy; inflation rates; higher education; tuition costs; Higher Education Act; undue hardship standard